2021
DOI: 10.31219/osf.io/wmkn3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superspreaders drive the largest outbreaks of hospital onset COVID-19 infection

Abstract: The SARS-CoV-2 virus has been noted both for its rapid spread, but also for the heterogeneity of transmission, with incidences noted of superspreading behaviour. We here applied a novel network reconstruction algorithm to infer patterns of viral transmission occurring between patients and health care workers (HCWs) in the largest clusters of COVID-19 infection identified during the first wave of the epidemic at Cambridge University Hospitals NHS Foundation Trust, UK. Based upon dates of individuals reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…This study demonstrates that retrospective analyses of genomic data is useful in some circumstances to guide future IPC practice, with results consistent with similar studies in the UK [7][8][9][10]. It remains to be seen whether the additional costs of generating and analysing this genomic data near real-time (<48hrs from sample to dissemination of results) are justified by additional IPC gains, or whether the rapid and rigorous application of gold standard epidemiological methods in response to fast accumulation of nosocomial PCR-based diagnoses is the key intervention.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study demonstrates that retrospective analyses of genomic data is useful in some circumstances to guide future IPC practice, with results consistent with similar studies in the UK [7][8][9][10]. It remains to be seen whether the additional costs of generating and analysing this genomic data near real-time (<48hrs from sample to dissemination of results) are justified by additional IPC gains, or whether the rapid and rigorous application of gold standard epidemiological methods in response to fast accumulation of nosocomial PCR-based diagnoses is the key intervention.…”
Section: Discussionsupporting
confidence: 86%
“…Individuals infected with identical or near-identical (≤1 SNP) viruses, are more likely to be linked in a transmission chain than those with more distantly related viruses, as demonstrated by previous retrospective studies that have utilised WGS to identify nosocomial infections and outbreaks. [7][8][9][10][11][12] We investigated whether sequencing could enhance epidemiological investigation of healthcare-associated SARS-CoV-2 acquisition in two areas: i) confirming/excluding nosocomial acquisition and ii) understanding the role of outbreaks in nosocomial acquisition. We highlight the benefits and pitfalls of this approach, to help guide local practice in individual centres.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are different from those in a smaller study focusing on a few large clusters in another UK hospital, where 20% of individuals caused 80% of transmission events. [11] Importantly, we find that hospitalacquired SARS-CoV-2 cases give rise to a greater number of secondary cases than community-onset community-associated cases. Cases admitted from the community already suspected as having COVID-19 will have been isolated in single cubicles or COVID-19 cohort areas more rapidly, thus limiting opportunities for onward transmission.…”
Section: Discussionmentioning
confidence: 62%
“…[10] In the time scale of an outbreak, a large proportion of individuals are infected by viruses too genetically similar to each other to distinguish genuine transmission events from unrelated infections. Furthermore, data from HCWs have rarely been included in previous analyses [11] and the relative role that patients and HCWs have played in fuelling hospital outbreaks in the UK remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Prior to the introduction of FFP3, HCW infection rates on "red" wards were greater than those on "green" wards, and also demonstrated no correlation with community case rates, suggesting infections resulted from direct patient care -in line with genomic evidence that a large proportion of HCW infections are transmitted from patients. [6] Some studies have suggested that staff infection rates merely reflect transmission in the community such that staff rates increase as community rates rise and are therefore inevitable. [7,8] This study highlights that this is only true for non-COVID-19 facing staff, with exposure to infected patients being the driving factor for infections in COVID-19 facing staff.…”
mentioning
confidence: 99%